Aptamer-Quantum Dots platform for SARS-CoV-2 viral particle detection with a fluorescence microscope - Radrizzani, M. (2024)
The virus is the smallest known replicative unit, usually in nanometerrange sizes. The most simple and sensitive detection assay involves molecular amplification of nucleic acids. This work shows a novel, straightforward detection assay based on the interaction of viral particles with fluorescent nanoconstructs without using enzymatic amplification, washing or separation steps. Fluorescent nanoconstructs are prepared with individual quantum dots of different emitting fluorescence, green and red, as a core. They are decorated with aptamers developed to recognise the receptor-binding region of the SARS-CoV-2 spike protein. Nanoconstructs can recognise SARS-CoV-2 viral particles fixed onto a coverglass generating aggregates. Meanwhile, SARS-CoV-2 viral particles/nanoconstructs complexes in solution yield macroaggregates, which can be visualised by a fluorescence microscope at low magnification. The method takes advantage of the enhanced affinity of homomultivalent interactions and light fluorescence signal amplification of quantum dots. The multiple molecular recognition allowed the detection of SARS-CoV-2 viral particles from a few microliters of patient swabs. This specific SARS-CoV- 2/nanoconstructs interaction generates insoluble and precipitating aggregates. By using a mixture of green and red fluorescent nanoconstructs, upon the viral particle interaction at a distance closer than 250 nm, they yield yellow fluorescence, which is easily identifiable by a fluorescence microscope. This is a consequence that they do not comply with the Rayleigh criterion, and in this way, washing and separation steps are not required. In addition, the larger size of aggregates allows one to easily recognise them at low magnification (200x), offering a sensitive, simple, and cheap alternative for viral detection.